Association between the fibrosis-4 and the risk of left ventricular aneurysm formation in acute ST-segment elevation myocardial infarction - Kai Zhang; Lihong Yang; Yonghui Zhao (Frontiers in Cardiovascular Medicine)
BackgroundLeft ventricular aneurysm (LVA) often occurs as a complication following an acute myocardial infarction. This research focused on assessing the ability of the fibrosis-4 (FIB-4) index to predict LVA formation in individuals with acute ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PCI).MethodsWe included 1,384 consecutive patients diagnosed with STEMI and compared their clinical and laboratory data between the LVA group and the non-LVA group. To determine the independent risk factors for LVA formation, multivariable logistic regression analysis was employed. Restricted cubic spline (RCS) analysis was conducted to evaluate the nonlinear relationship between FIB-4 index and LVA formation. The ROC curve was used to determine the predictive capability of the FIB-4 index and composite variable for LVA formation.ResultsLVA occurred in 12.7% of the population. An elevated FIB-4 index correlated with a higher occurrence of LVA (19% vs. 9.3%, P < 0.001). In the LVA group, the FIB-4 index was higher than in the non-LVA group [1.8 (1.1–4.6) vs. 3.5 (1.4–8.1), P < 0.001]. Analysis using multivariable logistic regression showed that the FIB-4 index independently correlated with LVA risk (OR =  1.73, P = 0.004). The analysis using RCS uncovered a nonlinear correlation between a higher FIB-4 index and a heightened risk of LVA (Nonlinear P = 0.009). Additionally, the area under the ROC curve for the FIB-4 index in predicting LVA was 0.617. The composite variable comprising the FIB-4 index, left ventricular ejection fraction (LVEF), estimated glomerular filtration rate (eGFR), and left anterior descending artery (LAD) as culprit vessel significantly improved the predictive power (C statistic = 0.722).ConclusionAn increased FIB-4 index was positively associated with LVA formation in patients with acute STEMI who underwent primary PCI.